The communication of leadership the design of leadership style - Charteris-Black, Jonathan (London Routledge, 2006)
With the crisis of leadership in the western democracies, there has been a growth of interest in how leaders outside of the west emerge and consolidate their positions. This book analyses the communication strategies of six charismatic non-western leaders: Mahatma Gandhi, Nelson Mandela, Fidel Castro, Ayatollah Khomeini, Mohammed Mahathir and Lee Kuan Yew. The book addresses the following questions in order to arrive at a better understanding of communication and leadership: How do leaders communicate? Do leaders communicate more by words, or actions? Do leaders have unique communication strategies? Are leaders moral beings, or impostors? The book describes how each of these leaders designed a unique style that integrated verbal and non-verbal modes of communication. It argues that leadership style is performed through the cumulative interaction of non-verbal modes ? dress, body language, physical possessions, symbols and symbolic actions ? with verbal strategies for communicating visions, values and legitimacy. In order to understand how each of these leaders undertakes a dramatic ?performance? of leadership, Jonathan Charteris-Black uses Erving Goffman?s notion of ?Front?. Noting the inherent similarities between the mutual dependency of actors with audiences and leaders with followers, the book suggests that leaders ? like actors ? use metaphors and symbols to satisfy followers? psychological and symbolic needs and that leadership is communicated through impression management, metaphor and media choices.
includes Bibliographical references p. (239-244)
Keywords: Communication